A Great Big Girl Like Me : The Films of Marie Dressler - Sturtevant, Victoria, 1973- (Book collections on Project MUSE., 2009)
In this study of Marie Dressler, MGM's most profitable movie star in the early 1930s, Victoria Sturtevant analyzes Dressler's use of her body to challenge Hollywood's standards for leading ladies. At five feet seven inches tall and two hundred pounds, Dressler often played ugly ducklings, old maids, doting mothers, and imperious dowagers. However, her body, her fearless physicality, and her athletic slapstick routines commanded the screen. Sturtevant interprets the meanings of Dressler's body by looking at her vaudeville career, her transgressive representation of an "unruly" yet sexual body in Emma and Christopher Bean, ideas of the body politic in the films Politics and Prosperity, and Dressler as a mythic body in Min and Bill and Tugboat Annie.